2022
DOI: 10.1039/d2sd00035k
|View full text |Cite
|
Sign up to set email alerts
|

Intercalating methylene blue in molecular beacon for sensitive detection of salivary TNF-α towards early diagnosis of oral cancer

Abstract: Oral cancer is the sixth most common cancer globally, and pro-inflammatory cytokines are associated with oral cancer development and progression. Monitoring of salivary pro-inflammatory cytokines is essential to the early...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Beacon conformational reconfiguration occurs spontaneously when an MB hybridizes with its complementary target DNA, mRNA, and microRNA, 125 resulting in fluorescence restoration. 126 Many studies have used MBs as early cancer diagnosis agents, 127 which may help cancer therapy by determining specific gene expression in real-time. 128 Graphene derivatives are one of the potential transfer agents for genetic materials.…”
Section: Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Beacon conformational reconfiguration occurs spontaneously when an MB hybridizes with its complementary target DNA, mRNA, and microRNA, 125 resulting in fluorescence restoration. 126 Many studies have used MBs as early cancer diagnosis agents, 127 which may help cancer therapy by determining specific gene expression in real-time. 128 Graphene derivatives are one of the potential transfer agents for genetic materials.…”
Section: Gene Deliverymentioning
confidence: 99%
“…Many studies have used MBs as early cancer diagnosis agents, 127 which may help cancer therapy by determining specific gene expression in real-time. 128 Graphene derivatives are one of the potential transfer agents for genetic materials.…”
Section: Gene Deliverymentioning
confidence: 99%
“…Label-free electrochemical detection of biomolecules either uses the change in the square wave voltammetry (SWV) reduction peak current of a redox probe or monitors the change in real and imaginary impedance (EIS) during immunorecognition events. Moreover, SWV-EIS transductions are considered more sensitive than commercially available ELISA kits [ 25 , 26 , 27 , 28 ], while amperometric sensing (current signal measurements) [ 29 , 30 , 31 , 32 ] and differential pulse voltammetry (DPV) [ 33 , 34 , 35 ] are considered advantageous as low-cost technologies and in good agreement with ELISA performance. Herein, several electrochemical studies using the Cys/GA reagents are reported and discussed ( Table 2 ).…”
Section: Electrochemical Immunosensorsmentioning
confidence: 99%